THE ELECTROMAGNETIC FIELD OF THE POINT HERTZIAN RADIATOR IN UNIAXIAL MAGNETIC CRYSTAL - Kanymgaziyeva, Ilmira (European Scientific Journal, ESJ, 2014)
Earlier received new analytical solution of the equation of Maxwell are expressed by several wave potentials, one of them is constructed by means of an integrated sine and a cosine. In this work asymptotic solution from the analytical solution of the equations of Maxwell for electromagnetic field strength of the emitter radiator of Hertz in uniaxial magnetic crystal are received.